Hypocenter dimension of 7.5 mw Palu earthquake using fractal approach. Issue 1 (October 2020) - Rasimeng, Syamsurijal; Alimuddin,; Rustadi,; Sinambela, Rudy Z.; Mandang, Idris; Bakri, Samsul; Zaenudin, Ahmad
Abstract: Research on the Palu earthquake in the period of August to October 2018 has been carried out in the Palu Koro Fault (PKF) zone with a hypocenter of 5-20 km. This study aims to determine the fractal dimensions of these earthquakes based on the relationship between logarithmic frequency and earthquake magnitude correlation introduced by Gutenberg-Richter. Statistical correlation between logarithmic frequency and earthquake magnitude was calculated using the inversion approach. Based on the calculation results obtained fractal dimension value of 1.0378, which describes the seismicity pattern at a depth of 5-20 km. It indicates that the earthquakes triggered by the movement in rupture segments which seen as points along the PKF zone.